Effects of Base Metal Preheating on the Microstructure, Mechanical Properties, and Corrosion Resistance of UNS S32750 SDSS Pulsed Nd:YAG Laser Welding - da Cruz Junior, Eli J.; Varasquim, Francisco M. F. A.; Crespo, Gillian S. [UNESP]; Ventrella, Vicente. A. [UNESP]; Zambon, Andrea; Calliari, Irene (MDPI, 2023)
Super duplex stainless steel has a microstructure consisting of equal proportions of austenite and ferrite. However, welding with Nd:YAG pulsed laser results in an imbalanced microstructure that compromises the steel’s properties. This paper studied the effects of preheating the base metal on pulsed Nd:YAG laser welding. Four conditions were evaluated (no preheating and heating at 100 °C, 200 °C, and 300 °C). The analysis included studying the microstructure, microhardness, and corrosion resistance. Preheating the base metals was found to be an effective method for increasing the volume fractions of austenite. The preheated samples showed an improvement in corrosion resistance compared to the untreated sample. The microhardness varied, with the ferrite amount being higher in the untreated sample.
Keywords: corrosion resistance; heat treatment; laser welding; microhardness; microstructure; super duplex stainless steel